Characterization of a novel galectin in Sarcoptes scabiei and its role in regulating macrophage functions - He, Ran; Zhang, Qian; Xu, Luyang; Guo, Maochuan; Gu, Xiaobin; Xie, Yue; Xu, Jing; Shen, Zhaoli (Frontiers in Microbiology, 2023)
Sarcoptes scabiei(S. scabiei) endanger human and other mammalian health. There has been limited research into S. scabiei pathogenic mechanism and the immunological interaction between S. scabiei and hosts. Galectins have critical roles in biological processes such as cell adhesion, signal transduction, and immune response mediation. Galectins of S. scabiei (SsGalectins) were cloned, expressed, and identified, and their transcriptional levels in S. scabiei were measured at various developmental stages. Fluorescent tissue localization was performed on SsGalectins of S. scabiei and scabies skin. Mouse AD model was constructed to evaluate the effect of rSsGalectins on the skin pathogenic changes. qPCR and ELISA were used to identify macrophage polarization-related components and to investigate the immunoregulatory effect of rSsGalectins on mouse macrophages. The results demonstrated that S. scabiei infection cause macrophage infiltration in scabies skin. The rSsGalectins displayed strong reactogenicity, and distinct genes of the SsGalectins were differently expressed in different developmental stages of S. scabiei. Fluorescence tissue localization revealed that the SsGalectins mainly were in the mouthparts, intestines, and body surface. Additionally, S. scabiei could secrete SsGalectins into the infected skin, proving that SsGalectins were excretion and secretion protein of S. scabiei. In the mouse atopic dermatitis (AD) model, cutaneous macrophage infiltration and inflammation increase after rSsGalectins injection. Simultaneously, when rSsGalectins acted on bone marrow-derived macrophages (BMDM), M1 macrophage-related polarization factors IL-1β, IL-6, and inducible nitric oxide synthase(iNOS) all increased, demonstrating that rSsGalectins can induce M1 polarization and produce pro-inflammatory cytokines. In conclusion, the SsGalectins are involved in the pathogenic process of S. scabiei by regulating the polarization of host macrophages to M1 type when S. scabiei invade the host and promoting the incidence and development of host inflammatory response. This study offers fresh light on the pathogenic process of scabies mites, investigates the immunological interaction mechanism between S. scabiei and the host, and offers new insights into S. scabiei prevention and therapy.